Using Agent-based Simulation for Safety: Fact-finding about a crowd accident to improve public space design - Liu, Yuanyuan; Kaneda, Toshiyuki (Collective Dynamics, 2020)
With the growing city density and large gatherings happening all over the world, crowd safety has become a new topic. This research discusses how to diagnosis and improve crowd safety in urban public space by analysing a real crowd accident that happened in Shanghai in 2014 using an agent-based simulator. Fact-finding analysis shows that insufficient capacity of the whole area, density difference in bottleneck stairs and lack of separation measurements in front of bottleneck stairs are the main causes of the accident. According to the media query towards the original space plan, we made two alternative plans in the bottleneck area and tested their performances.